Apolipoprotein (a) concentrations and susceptibility to coronary artery disease in patients with peripheral vascular disease. Issue 1 (January 1993) - Groves, P; Rees, A; Bishop, A; Morgan, R; Ruttley, M; Lewis, N; Lane, I; Hall, R
Abstract : OBJECTIVE–To investigate the relation between apolipoprotein(a) concentrations and angiographically defined coronary artery disease in patients with atheromatous peripheral vascular disease. DESIGN–40 consecutive patients were recruited at the time of admission for peripheral vascular surgery. All underwent clinical assessment and coronary arteriography. Apolipoprotein(a) concentrations were measured by an immunoradiometric assay. SETTING–Tertiary referral centre. SUBJECTS–Patients requiring surgical intervention for large vessel peripheral vascular disease. MAIN OUTCOME MEASURES–Presence or absence and severity and distribution of angiographically defined coronary artery disease. Measurement of circulating contractions of apolipoprotein(a) and other lipid indices. RESULTS–Coronary artery disease was absent in 11 patients (group 1), mild to moderate in 12 (group 2), and severe in 17 (group 3). The distribution of peripheral vascular disease and of standard lipid indices was similar in these three groups of patients. There was a significant difference in apolipoprotein(a) concentrations between the three groups, with concentrations progressively increasing with the severity of coronary artery disease (mean (95% confidence interval): group 1, 112 U/1 (52 to 242); group 2, 214 U/1 (129 to 355); group 3, 537 U/1 (271 to 1064) (analysis of variance p < 0.005). The prevalence of coronary artery disease was increased 7.4 fold in patients with apolipoprotein(a) concentrations that were greater than the cohort median (206 U/1) (p < 0.01). CONCLUSIONS–The results show an association between apolipoprotein(a) concentrations and angiographically defined coronary artery disease in patients with large vessel peripheral vascular disease. The findings imply differences in the pathogenesis of coronary and peripheral atheroma and suggest that the measurement of apolipoprotein(a) may prove a useful additional tool in the risk factor assessment of patients undergoing peripheral vascular surgery.